A comparative study of predicting oxygen transfer in weirs and water jets in cross-flows. Issue 1 (24th May 2017) - Jahromi, Mina Esmi; Khiadani, Mehdi; Shukla, Sanjay Kumar
Abstract : A water jet in a cross-flow drives a substantial content of oxygen into a water body through air ingression. An experimental study was conducted on the oxygen-transfer capacity of a water jet in a cross-flow in which the major influential parameters of the water jet and the receiving water were systematically varied. The mechanism of air entrainment and the hydrodynamic behaviour of the generated two-phase air–water flow reveal major similarities between a low-drop sharp-crested weir aeration system and a jet in a cross-flow. Notwithstanding the cross-flow as the main source of distinction, similar to weir systems, equations were developed to predict the oxygen-transfer efficiency of a water jet in a cross-flow. Amendments were applied to account for the cross-flow characteristics as well as experimental conditions. The results indicated that cross-flow characteristics such as depth and velocity should be included in predictive equations as they influence aeration efficiency. However, minor modifications of independent parameters were promising in some cases. Furthermore, an equation was developed for the estimation of oxygen-transfer efficiency using dimensional analysis.